ANALISIS PENGARUH ROA, ROE, CURRENT RATIO, DAN ITO DALAM MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Dandi Arista Keliat; Helen; Gina maria krismansa; Tuty Nainggolan; Jaka Syahputra (Journal Accounting International Mount Hope, 2024)
The aim of this research is to determine the influence of ROA, ROE, Current Ratio, and ITO in predicting changes in profits in consumer goods industry companies listed on the Indonesian Stock Exchange for the 2018-2021 period. iiThis research was carried out iion iiconsumer iigoods iicompanies iiwhich are registered iion iiEffect Exchange iiIndonesia iivia iiwebsite iiwww.idx.co.id. iiThe time of this research is from the 2nd month of May 2023 to November 2023. iiThis approach uses a quantitative approach, the quantitative approach is a positivism-based method which is used to study a particular population and a particular sample. In total there are 74 companies in the consumer goods industry sector registered in the 2018-2021 period. i The results of this research show that there is no partially significant influence between Return on Assets on Changes in Profit, there is no partially significant influence between Return on Equity on Changes in Profit, there is a partially significant influence between Current Ratio on Changes in Profit, there is a partially significant influence between Inventory Turnover on Changes in Profit. Simultaneously Return on Assets, Return on Equity, Current Ratio, and Inventory Turnover have a significant effect on Profit Changes.